2018
DOI: 10.1037/mgr0000072
|View full text |Cite
|
Sign up to set email alerts
|

Leadership in higher education: Opportunities and challenges for psychologist-managers.

Abstract: This article provides ideas and recommendations for psychologist-managers seeking to transition from the private sector to institutions of higher education. We first describe the differences between the cultures of academia and the private sector and then distinguish between traditional and nontraditional leadership roles at a university or college. We also discuss the challenges and opportunities faced by future academic leaders. Throughout this article, we describe the knowledge and skill sets that make psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 9 publications
0
11
0
3
Order By: Relevance
“…These struggles and trade-offs were clearly visible to current colleagues, creating an image of a professional who does not fit the profile of a future academic leader. Academic leaders, irrespective of the pressures they face, are expected to have a strong reputation for collegiality, patience, and good listening skills that would enable them to be successful in enacting the bottom-up governance approach typical for academia (Wang & Frederick, 2018). It is important, therefore, for all business schools to implement practices that support research productivity in general and international mobility in particular as another mechanism of career development for female faculty.…”
Section: Mobility and Academic Promotionmentioning
confidence: 99%
“…These struggles and trade-offs were clearly visible to current colleagues, creating an image of a professional who does not fit the profile of a future academic leader. Academic leaders, irrespective of the pressures they face, are expected to have a strong reputation for collegiality, patience, and good listening skills that would enable them to be successful in enacting the bottom-up governance approach typical for academia (Wang & Frederick, 2018). It is important, therefore, for all business schools to implement practices that support research productivity in general and international mobility in particular as another mechanism of career development for female faculty.…”
Section: Mobility and Academic Promotionmentioning
confidence: 99%
“…It has been suggested that mental health practitioners make dynamic leaders in higher education settings (Miller, 2016;Wang & Frederick, 2018). There is, however, a lack of leadership style inquiry in the mental health field (Aarons, 2006;Gharabaghi & Anderson-Nathe, 2016;Kois et al, 2015).…”
Section: Leadership In Marriage and Family Therapy Programs And Othermentioning
confidence: 99%
“…In those medieval periods, monks and religious leaders focused on liberal arts (writings of Plato and Aristotle, for example), philosophy and theology (Good & Teller, 1969). These medieval monastic communities provided learning environments and preserved libraries, and both of these actions would impact the development of educational efforts across western Europe and beyond for centuries to follow (Wang & Frederick, 2018). Ultimately, civil governments became interested in fostering learning environments that provided education to broader constituencies.…”
Section: History Of the Organizationsmentioning
confidence: 99%
“…Bureaucratic elements such as the utilization of numerous committees, involving both faculty and staff creates an often slow, but fairly thorough process (Wang & Frederick, 2018). In reaction to this perceived cumbersome and slow process within bureaucracies, pressures from external economic factors have pushed modern institutions of higher learning to function more like business organizations, whereby smaller groups of trustees or Board members operate with a tight group of professional executives to make quick decisions to further the institutions momentum toward achieving strategic objectives (Harper & Jackson, 2011).…”
Section: Organizational Analysismentioning
confidence: 99%
See 1 more Smart Citation